Attraction of Individuals to Russian Stock Market - A. P. Garnov; E. V. Afanasyev (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
The article studies investment activity of the population on Russian stock market in 2015–2022. The research used data and analytical information of the Federal Service of State Statistics, the Central Bank of the Russian Federation, the Moscow Exchange, NAFI Analytical Center. The authors ground the importance of attracting individuals to the stock market in conditions of economic sanctions introduced against Russia. They come to the conclusion that the growth in the number of private investors and the amount of funds on individual investment accounts are influenced by concessional taxation, higher real incomes of the population, improving financial literacy and trust to the stock market, as well as simplifying registration and trade on stock market and rising profitability of investing into shares and bonds. The adverse impact on the number of brokers’ clients and the amount of funds on individual investment accounts is rendered by deposit rates in banks, dropping confidence to stock market and deterioration in conditions for saving building. The authors provide recommendations on developing the stock market in Russia, which include extension of concessional taxation on transactions with securities by individuals, better accessibility of digital tools and services, for instance by the ‘Marketplace’ project, higher level of finance literacy of the population, especially in rural and remote regions.